1999
DOI: 10.1007/s002679900183
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Water Hyacinth Under Conditions of Maintenance Management: Can Herbicides and Insects Be Integrated?

Abstract: / We hypothesized that repeated herbicidal (maintenance) control of water hyacinth infestations in Florida suppressed biological control agent populations, especially the weevils Neochetina eichhorniae and N. bruchi. We therefore sampled water hyacinth and weevil populations at 54 sites distributed statewide. Half were under maintenance control, half were not treated with herbicides. General site conditions were assessed, demographic data were collected on weevil and plant populations, the reproductive conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 18 publications
6
109
1
1
Order By: Relevance
“…By the result of this effect it drastically increases the water loss exposing the plant to pathogens finally reducing the plant growth (Julien, 2000). They are the most effective biological controller of water hyacinth when compared with other arthropods (Center et al, 1999b;Center and Van, 1989;DeLoach and Cordo, 1976). Among around 30 countries these weevils have been successfully utilized to control water hyacinth due to their host specific nature and effectiveness (Center et al, 2002;Firehun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By the result of this effect it drastically increases the water loss exposing the plant to pathogens finally reducing the plant growth (Julien, 2000). They are the most effective biological controller of water hyacinth when compared with other arthropods (Center et al, 1999b;Center and Van, 1989;DeLoach and Cordo, 1976). Among around 30 countries these weevils have been successfully utilized to control water hyacinth due to their host specific nature and effectiveness (Center et al, 2002;Firehun et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these facts, biological control is often ignored by some land managers as an asset for cutting costs, in part because of the difficulty or lack of information on integrating biological control into existing management programs. This is typified in Florida where, despite the widespread presence of damaging insect biological control agents on E. crassipes, there is no intentional integration with herbicides because many managers find it easier and simpler to follow routine and regular spray programs against aquatic weed populations (Center et al, 1999). Integrated control is technically feasible against E. crassipes as demonstrated by Haag et al (1988) and Haag and Habeck (1991) who designed and evaluated an integrated approach for E. crassipes using herbicides and biological control.…”
Section: Introductionmentioning
confidence: 99%
“…Samea multiplicalis (Guenée) (Lepidoptera: Crambidae) and Synclita obliteratis (Walker) (Lepidoptera: Crambidae) are two abundant generalist herbivores whose host range includes E. crassipes (Knopf and Habeck, 1976;Habeck et al, 1986). Evaluation studies have focused primarily on N. eichhorniae and N. bruchi using before and after release field studies with no-or non-persistent controls, or caged-tank studies with controls (Center and Durden, 1986;Center et al, 1999). It is difficult to maintain controls under field conditions because of agent dispersal and the presence of considerable biotic and abiotic environmental variation among sites.…”
Section: Introductionmentioning
confidence: 99%
“…Center et al (1999) showed that sustained herbivory of E. crassipes reduced proportionately biomass and floral structures. Normally E. crassipes will out-compete other floating aquatic plants; Center et al (2005) measured E. crassipes biomass production and compared to Pistia stratiotes and found that E. crassipes biomass yield was 41 times that of Pistia stratiotes.…”
Section: Controlmentioning
confidence: 99%